Gorham's disease: clinical case - Pedro Sá; Pedro Marques; Carolina Oliveira; André Sá Rodrigues; Nelson Amorim; Rui Pinto (Revista Brasileira de Ortopedia, 2015)
Gorham's disease, also known as idiopathic massive osteolysis, is a rare pathological condition characterized by vascular proliferation that results in destruction and reabsorption of the bone matrix, of unknown etiology. It was first described by Jackson in 1838, but it was Gorham and Stout, in 1955, who defined this disease as a specific entity. It has variable clinical presentation and generally has progressive behavior. Controversy continues regarding the treatment and there is no standard treatment. This pathological condition generally presents a favorable prognosis. Here, a case of Gorham's disease with involvement of the left hip is presented, in a male patient without relevant antecedents.